Screening for schizophrenia in initial prodromal phase: Detecting the sub-threshold psychosis - Razali, Salleh Mohd; Abidin, Zarina Zainan; Othman, Zahiruddin; Yassin, Mohd Azhar Mohd (Elsevier, 2015)
Objectives: The aim of the study is to screen and evaluate the efficacy of the screening tools in detecting subjects with sub-threshold psychosis among asymptomatic individuals at genetic risk, as compared with persons in the general public. Methods: This was a two-stage study of the relatives of patients with schizophrenia and general individuals. Subjects were screened with a Screening Questionnaire (SQ) and General Health Questionnaires (GHQ-12) in the initial stage. Those who screened positive were reassessed using the Comprehensive Assessment of At-Risk Mental State (CAARMS) in the second stage. Results: A total of 190 (29%) subjects initially screened positive from a sample of 660 individuals. The proportion of persons in the general public (63%) who progressed to the second stage was significantly higher than at-risk relatives (37.4%) (X2 = 17.028, df = 1, p < 0.001). After final assessment, about 4% of the sample was positive; subjects at sub-threshold UHR (ultra-high risk) was higher (69%) than subjects at UHR (31%). Detection rate was higher when both GHQ and SQ (26.4%) measures were positive in the initial screening. In both categories of sub-threshold psychosis, the percentage of subjects at genetic risk was higher (62%), and the proportion steadily increased as the psychosis progressed. Conclusion: The prevalence of sub-threshold psychosis was higher in subjects at genetic risk. Clinical assessment following a self-report questionnaire should be mandatory as the rate of false positive results is high. The SQ has poor validation indexes, which is partly contributed to low detection rate and the GHQ is not suitable for screening early psychosis.